UNUSUAL PRESENTATION OF A CASE OF TAKAYASU ARTERITIS - Shabbir, Adnan; Mohyudin, Adil; Rao, Khushbakht Javeria; Tayyab, Ghias Un Nabi; Abbasi, Abu Fahad (Journal of Ayub Medical College Abbottabad, 2019)
Takayasu arteritis is a rare disease of medium size and large vessels causing granulomatous inflammation of the involved territory. The most usual area involved is the arch of the aorta and its major branches. We came across an atypical presentation of this rare disease in our medicine department at Lahore General Hospital. A 52-year-old male presented with complaints of vertigo, bilateral upper limb cramps on physical activity. On examination, pulses were absent bilaterally in upper limbs. On CT angiography brachiocephalic and left subclavian arteries were not visualized. Inflammatory markers were not raised to the extent indicating a very aggressive disease. The patient was not meeting the age limit as described by Ishikawa diagnostic criteria. The patient was referred to the cardiovascular surgery department for revascularization. Keywords: Takayasu arteritis; Ishikawa criteria; Aortic arch syndrome